Psychological Analysis of Students in The Inline Lecture Process at STIE Bina Karya - Imelda Mardayanti (IHSA Institute, 2021)
The application of online learning is affected by social distancing in the world of education, especially among students, resulting in poor student health. As a result, students do not interact socially with the surrounding environment, reduce learning effectiveness and feel bored. This journal aims to provide an overview and analyze online learning models on the mental health of students affected by social disstanding. The research approach used is qualitative in the form of a Creswell model of literature. Data sources from online learning literature, Student mental health, COVID-19. Data collection techniques by conducting searches on related literature, both manually and digitally. The data analysis technique used the Moleong model analysis. The results show that online learning is not effective among students because students' mental health is disturbed by the application which currently plays an important role in the world of education but the application of the online learning system is not as easy as imagined, there are several aspects that must be met first.